Hijab (Veil) from the Islamic Perspective: An Interpretive Analysis from the Quran and Scholars' Views - Mohamed Sulthan Ismiya Begum (MAQOLAT: Journal of Islamic Studies, 2025)
This research examines the concept of the Hijab (veil) from both Quranic and scholarly perspectives, with a particular focus on its role in promoting justice and equity. Utilizing a qualitative research methodology, the study draws on primary sources, including key Quranic verses such as Surah An-Nur (24:31) and Surah Al-Ahzab (33:59), which provide foundational principles regarding modesty, dignity, and ethical conduct. Secondary sources, including books, journal articles, and online publications, are analyzed to contextualize scholarly interpretations and explore the broader significance of the Hijab.An interpretive research approach is employed to uncover the multifaceted meanings of the Hijab as a spiritual, social, and ethical practice. Classical and contemporary Islamic scholars’ perspectives are critically examined to highlight the Hijab’s dual function as a personal act of devotion and a societal symbol of identity and respect. The findings demonstrate that the Hijab is deeply rooted in Islamic teachings, reflecting principles of justice, equity, and mutual respect. Furthermore, the study addresses prevalent misconceptions about the Hijab and its association with gender roles, illustrating its broader implications within Islamic thought. This research contributes to a nuanced understanding of the Hijab, emphasizing its enduring relevance and its role in fostering justice and equity within contemporary Muslim societies.